2018
DOI: 10.1029/2018jb015986
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Noise Monitoring of Seismic Velocity Around the Longmenshan Fault Zone From 10 Years of Continuous Observation

Abstract: We present 10‐year continuous seismic velocity changes from 2007 to 2017 around the Longmenshan fault zone, where the 2008 Mw 7.9 Wenchuan earthquake and the 2013 Mw 6.6 Lushan earthquake occurred. We collected continuous waveforms recorded by 20 broadband stations covering the entire Longmenshan fault zone and used three‐component ambient noise correlation techniques to measure the velocity changes in four different period bands. Our results show that a significant drop, 0.04–0.06%, occurred in the coseismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
(137 reference statements)
3
10
0
Order By: Relevance
“…For the type of study we are conducting, this change typically results in a net decrease in the observed velocity due to the ambient noise being dominated by surface waves (Clements & Denolle, 2018; Kim & Lekic, 2019). Such effects have been observed in other recent studies of ambient seismic noise (e.g., Civilini et al., 2020; Clements & Denolle, 2018; Fores et al., 2018; Hillers et al., 2014; Joubert et al., 2018; Kim & Lekic, 2019; Lecocq et al., 2017; Liu et al., 2018; Rivet et al., 2015; Sens‐Schönfelder & Wegler, 2006; Viens & Van Houtte, 2020; Viens et al., 2018; Voisin et al., 2016; Q. Y. Wang et al., 2017), but our work extends the analysis to higher frequencies and allows comparison with other types of environmental data. Temperature changes at the surface are also known to drive seismic‐velocity changes at depth, as has been observed in a number of previous ambient‐noise studies, again mostly working at lower frequencies, including those by Hillers et al.…”
Section: Introductionsupporting
confidence: 69%
“…For the type of study we are conducting, this change typically results in a net decrease in the observed velocity due to the ambient noise being dominated by surface waves (Clements & Denolle, 2018; Kim & Lekic, 2019). Such effects have been observed in other recent studies of ambient seismic noise (e.g., Civilini et al., 2020; Clements & Denolle, 2018; Fores et al., 2018; Hillers et al., 2014; Joubert et al., 2018; Kim & Lekic, 2019; Lecocq et al., 2017; Liu et al., 2018; Rivet et al., 2015; Sens‐Schönfelder & Wegler, 2006; Viens & Van Houtte, 2020; Viens et al., 2018; Voisin et al., 2016; Q. Y. Wang et al., 2017), but our work extends the analysis to higher frequencies and allows comparison with other types of environmental data. Temperature changes at the surface are also known to drive seismic‐velocity changes at depth, as has been observed in a number of previous ambient‐noise studies, again mostly working at lower frequencies, including those by Hillers et al.…”
Section: Introductionsupporting
confidence: 69%
“…Ambient noise interferometry has been widely used to detect seismic velocity changes ( dv/v ) in response to internal crustal processes, such as volcanic unrests (Brenguier, Shapiro, et al., 2008; Feng et al., 2020; Obermann, Planès, Larose, & Campillo, 2013; Olivier et al., 2019), fault zone damage and healing (Brenguier, Campillo, et al., 2008; Hillers et al., 2019; Liu et al., 2018; Obermann et al., 2014; Viens et al., 2018; Wang et al., 2019; Wegler & Sens‐Schönfelder, 2007; Yu & Hung, 2012), basin water storage (Berbellini et al., 2021; Clements & Denolle, 2018; Lecocq et al., 2017), and ice sheet loading/melting dynamics (Mordret et al., 2016). Such seismic velocity variations are also known to be complex since they could originate from multiple concurrent causes including external environmental forces.…”
Section: Introductionmentioning
confidence: 99%
“…Because different rocks or structures respond differently to the internal and external loadings, monitoring the crustal response can also help to identify local structure anomalies and understand wave propagation and attenuation (Wang et al., 2017). More specifically, measurements of the temporal changes of seismic velocity can shed light on the fault zone coseismic damage and postseismic healing (Brenguier et al., 2008; Liu, Huang, et al., 2018; Wu, 2016), volcanic eruption early warning (Brenguier et al., 2008; Duputel et al., 2009), groundwater levels (Clements & Denolle, 2018; Lecocq et al., 2017), climatological parameters such as precipitation (Sens‐Schönfelder & Wegler, 2006), temperature (Meier et al., 2010; Sens‐Schönfelder & Larose, 2008), and atmospheric pressure (Niu et al., 2008; Silver et al., 2007), solid earth tidal (De Fazio et al., 1973; Mao et al., 2019) and oceanic tidal deformation (Hillers et al., 2015; Yamamura et al., 2003), and instrumental errors (Stehly et al., 2007; Sens‐Schönfelder, 2008). Taking advantage of long‐term dense seismic station deployments, a systematic investigation of seismic velocity variation can improve our understanding of the crustal response to the climatological loadings.…”
Section: Introductionmentioning
confidence: 99%